1978
DOI: 10.1007/bf02533615
|View full text |Cite
|
Sign up to set email alerts
|

Identification of vasopressor phospholipid in crude soybean lecithin

Abstract: The vasopressor phospholipid in crude soybean lecithin was isolated by column chromatography on Sephadex LH-20. It represented 0.1% of crude soybean lecithin. The isolated phospholipid was identified to be lysophosphatidic acid by gas chromatography-mass spectrometry analysis of TMS-deacylated product and acetolysis product. Nuclear magnetic resonance analysis favored the 1-monoacyl isomer over the 2-isomer. By enzymic determination with L-3-glycerophosphate dehydrogenase, the isolated phospholipid was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 20 publications
0
40
0
1
Order By: Relevance
“…The potent cardio vascular activity of lysophosphatidic acid has been described in our own papers (11,21,22).…”
Section: Resultsmentioning
confidence: 81%
“…The potent cardio vascular activity of lysophosphatidic acid has been described in our own papers (11,21,22).…”
Section: Resultsmentioning
confidence: 81%
“…It was reported that unknown components of soybean lecithin regulate vasoactivity. 4) Further studies revealed that the active ingredients in lecithin were LPAs. LPAs showed differential regulation of vasoactivity, which is dependent on animal species.…”
Section: In Vitro and In Vivo Biological Activities Of Lpas In Foodstmentioning
confidence: 99%
“…Tokumura et al 4) first reported a novel component in a soybean lecithin fraction showing vasopressor activity in rats. 4) In further studies, they determined that the unknown active ingredient in lecithin was LPA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La première démonstration de l'existence d'un LPA bioactif remonte à 1963 où W. Vogt démontra que le LPA était impliqué dans l'effet vasoconstricteur induit par des extraits d'intestin de grenouille sur des cellules musculaires lisses de lapin [1]. Plusieurs années après, en 1978, il fut montré que l'injection intraveineuse de LPA conduisait à des effets rapides sur la pression artérielle [2]. À la même période, le LPA, connu comme un puissant facteur pro-agrégant [3], était mis en évidence dans le sang lors de l'agrégation plaquettaire [4].…”
unclassified